4T Zikr in Anxiety Reduction in Acute Coronary Syndrome Patients - Sukarni Sukarni; Mardiyono Mardiyono; Made Desak Wenten Parwati (Poltekkes Kemenkes Semarang, 2014)
Anxiety is a psychological problem that often arises in heart disease, especially in patients with acute coronary syndromes. Anxiety could prolong the healing process of ACS and increase the cost of care and treatment. Purpose of the study was to evaluaste the effect of 4T Zikr on anxiety in patients with ACS in the CICU. This research was a quasi-experimental two group pre post design. 64 subjects were recruited by purposive sampling; 28 subjects in intervention group and 28 subjects in control group. Anxiety was measured by NRS 0-10. 4T zikr composes of subhanallah, alhamdulillah, allahuakbar and laailahaillah with intensity 60 dB, beat rate 60-80 mm, pitch 220-800 Hz, volume 4-5 for 30 minutes. The results show that 4T zikr could reduce anxiety at 12 hours, 24 hours, 36 hours, 48 hours, 60 hours, and 72 hours in patients with ACS (p less than 0,05). There were significant differences in anxiety reduction at 24 hours (p less than 0,001) and 72 hours (p less than 0,001) between group after 4T zikkr in patients with ACS. In conclusion, 4T zikr can reduce anxiety within 72 hours after admission in patients with ACS.